DISCOHAT: An Acronym to Describe the Spectrum of Symptoms Related to Bilateral Vestibulopathy - Paredis, Sophie; van Stiphout, Lisa; Remmen, Eva; Strupp, Michael; Gerards, Marie-Cecile; Kingma, Herman; Van Rompaey, Vincent; Fornos, Angelica-Perez; Guinand, Nils; van de Berg, Raymond (Frontiers in Neurology, 2021)
Objective: To assess the prevalence of each symptom listed in the acronym DISCOHAT (worsening of symptoms in Darkness and/or uneven ground, Imbalance, Supermarket effect, Cognitive complaints, Oscillopsia, Head movements worsen symptoms, Autonomic complaints and Tiredness) in patients with bilateral vestibulopathy (BVP), compared to patients with unilateral vestibulopathy (UVP). Methods: A descriptive case-control study was performed on BVP and UVP patients who were evaluated for their vestibular symptoms by two of the authors (RvdB, MCG) at a tertiary referral center, between 2017 and 2020. During history taking, the presence of each DISCOHAT symptom was checked and included in the electronic health record. Presence of a symptom was categorized into: “present”, “not present” and “missing”. Results: Sixty-six BVP patients and 144 UVP patients were included in this study. Prevalence of single DISCOHAT symptoms varied from 52-92% in BVP patients and 18-75% in UVP patients. Patients with BVP significantly more often reported “worsening of symptoms in darkness”, “imbalance”, “oscillopsia” and “worsening of symptoms with fast head movements”, than UVP patients (p < 0.004). Conclusion: The DISCOHAT acronym is able to capture a wide spectrum of symptoms related to vestibulopathy, while it is easy and quickly to use in clinic. Application of this acronym might facilitate a more thorough and uniform assessment of bilateral vestibulopathy, within and between vestibular clinics worldwide.